ByzRev 06.2024.070: Nina-Maria Wanek, Cultural Transfer of Music Between Byzantium and the West:: The Case of the Chants of the So-Called Missa Graeca (Byzantina Austaliensia 27). Leiden: Brill 2024. - Spyrakou, Evangelia (The Byzantine Review, 2024)
Nina-Maria Wanek, Cultural Transfer of Music Between Byzantium and the West: The Case of the Chants of the So-Called Missa Graeca (Byzantina Austaliensia 27). Leiden: Brill 2024. xxiv+661 pp. – ISBN 978-90-04-51307-5 (€ 239.00 excl. VAT)